2018
DOI: 10.1002/pola.29078
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide modification of biomaterials using supramolecular additives

Abstract: Biomaterials based on non‐active polymers functionalized with antimicrobial agents by covalent modification or mixing are currently regarded as high potential solutions to prevent biomaterial associated infections that are major causes of biomedical device failure. Herewith a strategy is proposed in which antimicrobial materials are prepared by simply mixing‐and‐matching of ureido‐pyrimidinone (UPy) based supramolecular polymers with antimicrobial peptides (AMPs) modified with the same UPy‐moiety. The N‐termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…In addition, it may lead to cracking of the microfibres, hence an increase in the surface area for the oxidative degradation induced by the host inflammatory response. Theoretically, to solve this drawback, one could modify the degradation process by using a slower degrading UPy elastomer and take advantage of its potential for bioactivation and, for example, adding factors to accelerate tissue ingrowth [23,35,36]. The degradation process is also modulated by the vigour and nature of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it may lead to cracking of the microfibres, hence an increase in the surface area for the oxidative degradation induced by the host inflammatory response. Theoretically, to solve this drawback, one could modify the degradation process by using a slower degrading UPy elastomer and take advantage of its potential for bioactivation and, for example, adding factors to accelerate tissue ingrowth [23,35,36]. The degradation process is also modulated by the vigour and nature of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Solution‐cast films on 14‐mm glass coverslips were secured in an adapted Transwell as described before and sterilized under UV for 15 min. Endothelial cells were seeded at a density of 40.000 cells cm −2 and smooth muscle cells at 25.000 cm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been recently shown that antibiotic-resistant bacteria show a high frequency of collateral (increased) sensitivity to AMPs [ 110 ]. Antimicrobial peptides have been incorporated into biomaterials using different approaches such as through functionalization of thermoresponsive hydrogels [ 111 ], electrospinning [ 112 ], supramolecular interactions [ 113 ], and through the Layer-by-Layer assembly technique [ 114 ].…”
Section: Lbl For Antimicrobial Peptides Encapsulationmentioning
confidence: 99%